Profil Kemampuan Literasi Sains Siswa Pada Materi Perubahan Lingkungan Melalui Model Pembelajaran Learning Cycle Berbantu Media Padlet - Nining Nining; Sri Hartati; Meti Maspupah (Jurnal Pendidikan Indonesia, 2025)
Scientific literacy is a key 21st-century competency that needs to be developed in education, particularly in relation to environmental change issues. However, the results of PISA 2022 indicate that Indonesian students’ scientific literacy achievement remains low. This study aims to analyze the effect of the learning cycle model assisted by Padlet media on high school students’ scientific literacy skills in environmental change material. The research method used was quantitative with a quasi-experimental design of the pretest-posttest control group type. The sample consisted of 60 tenth-grade students, divided into an experimental class applying the learning cycle model with Padlet and a control class using conventional learning. The data collection instrument was a scientific literacy test that had been validated and proven reliable. Data analysis was conducted using t-tests and effect size measurements. The results showed no significant difference between the experimental and control classes. This finding indicates that the integration of the learning cycle model and Padlet was less effective in improving students’ scientific literacy. Theoretically, this research reinforces the relevance of constructivist learning combined with digital media. Practically, the findings can serve as recommendations for teachers to optimize the use of technology in science learning. Future research is suggested to expand the population, include additional variables, and combine quantitative and qualitative approaches to obtain a more comprehensive understanding.